2020
DOI: 10.1093/mnras/staa1046
|View full text |Cite
|
Sign up to set email alerts
|

Simulating diverse instabilities of dust in magnetized gas

Abstract: Recently Squire & Hopkins (2018b) showed that charged dust grains moving through magnetized gas under the influence of any external force (e.g. radiation pressure, gravity) are subject to a spectrum of instabilities. Qualitatively distinct instability families are associated with different Alfvén or magnetosonic waves and drift or gyro motion. We present a suite of simulations exploring these instabilities, for grains in a homogeneous medium subject to an external acceleration. We vary parameters such as the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 56 publications
6
41
0
Order By: Relevance
“…It has been predicted that negatively charged grains may affect the star formation efficiency due to gyroresonance effects with MHD waves propagating inside MCs (Pilipp et al 1987;Nakano 1998;Falceta-Gonçalves et al 2003;Hopkins et al 2020). For instance, Chapman & Wardle (2006) demonstrated that C-type MHD shocks profiles are deeply affected by the presence of a population of charged grains; Pandey & Vladimirov (2019) have recently shown that the Kevin-Helmholz instability in MCs depends on the dust charge density and size distribution; and Wardle (2007) and Pinto et al (2008) derived the modified coefficients for non-ideal MHD effects (Ohmic resistivity, and ambipolar and Hall diffusion) in the presence of charged dust grains.…”
Section: and Ismentioning
confidence: 99%
“…It has been predicted that negatively charged grains may affect the star formation efficiency due to gyroresonance effects with MHD waves propagating inside MCs (Pilipp et al 1987;Nakano 1998;Falceta-Gonçalves et al 2003;Hopkins et al 2020). For instance, Chapman & Wardle (2006) demonstrated that C-type MHD shocks profiles are deeply affected by the presence of a population of charged grains; Pandey & Vladimirov (2019) have recently shown that the Kevin-Helmholz instability in MCs depends on the dust charge density and size distribution; and Wardle (2007) and Pinto et al (2008) derived the modified coefficients for non-ideal MHD effects (Ohmic resistivity, and ambipolar and Hall diffusion) in the presence of charged dust grains.…”
Section: and Ismentioning
confidence: 99%
“…This effect was seen and diagnosed in detail in the CR streaming-instability simulations of Holcomb & Spitkovsky (2019), where they noted that CRs with an initial drift velocity that is too large (approaching c) are inefficiently self-confined, because the wave scattering only isotropizes particles with one sign of ξ . However, the non-linear saturation of the dust instability presents significant uncertainties; if the saturation is quasi-turbulent in nature, as suggested by the simulations of Seligman, Hopkins & Squire (2019), Hopkins et al (2020c) (albeit in a different regimes), it seems implausible that only one wave polarization would be present in the saturated state. In that case, fluctuations induced by the dust could more efficiently isotropize CRs.…”
Section: Polarizationmentioning
confidence: 99%
“…The most obvious candidate is by exciting some type of turbulence, which scatters dust particles sufficiently to shut off the instability's drive. The simulations of Hopkins et al (2020c) suggest that a simple saturation criterion is when a characteristic turnover time at the scale of interest is equal to the instability growth rate, which leads to an estimate of the power in small scale parallel fluctuations δ B 2 /B 2 ∼ ( /ω A ) 2 , where /ω A is the growth rate of the dust instability normalized by the Alfvén frequency at the chosen scale. This implies the CR diffusivity…”
Section: Enhanced Cosmic Ray Scattering Through Dust-excited Alfvén Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Collins 1989), plasma instabilities (e.g. Melrose 1980), or related dust instabilities (Moseley, Seligman, Hopkins & Squire 2019;Hopkins, Squire & Seligman 2020).…”
Section: Introductionmentioning
confidence: 99%